PENGARUH PERBANDINGAN MEDIA TANAM DAN KONSENTRASI ZAT PENGATUR TUMBUH (ZPT) TERHADAP PERBANYAKAN BENIH KENTANG (Solanum tuberosum L.) G-0 DARI SPROUT - Sumatera Tarigan; Meriksa Sembiring; Roida Ervina Sinaga; Lea Primaret Ketaren (Universitas Quality, 2021)
This reserch aims to determine the effect of comparison of planting media and and growth regulator concentration on the growth and propagation of G-0 Potato seeds. This research was carried out in the Screen house of the Raya Village garden, Berastagi District, Karo Regency, North Sumatra Province, with a place of ± 1,300 m asl. This research was carried out from January to April 2019. This reserch used the Factorial Randomized Block Design method of two treatment factors, namely the comparison treatment of planting media with the symbol